Twelve‐lead and signal‐averaged electrocardiographic parameters among beta‐thalassemia major patients - Patsourakos, Dimitrios; Gatzoulis, Konstantinos A.; Aggeli, Constantina; Delicou, Sophia; Dimitroglou, Yannis; Xydaki, Katerina; Toutouzas, Konstantinos; Androulakis, Aristeidis; Tousoulis, Dimitrios (Journal of arrhythmia, 2020)
Background The majority of beta thalassemia major (β‐TM) patients suffer from cardiac disease, while a significant proportion of them die suddenly. Twelve‐lead and signal‐averaged electrocardiography (SAECG) are simple, inexpensive, readily available tools for identifying an unfavorable arrhythmiological substrate by detecting the presence of arrhythmias, conduction abnormalities, and late potentials (LPs) in these patients. Methods A total of 47 β‐TM patients and 30 healthy controls were submitted to 12‐lead and signal‐averaged electrocardiography. Basic electrocardiographic parameters and prevalence of LPs were recorded. Basic echocardiographic parameters were estimated by transthoracic echocardiography. T2* was calculated by cardiac magnetic resonance imaging wherever available. Results β‐TM patients demonstrated a more prolonged PR interval (167.74 msec vs 147.07 msec) (P = .043), a higher prevalence of PR prolongation (21.05% vs 0%) (P = .013), and a higher prevalence of LPs (18/47, 38.3% vs 2/30, 6.7%) (P = .002) compared with controls. The prevalence of atrial fibrillation among b‐TM patients was estimated at 10.64%. Patients had also greater E/e′ ratio (8.35, SD = 2.2 vs 7, SD = 2.07) (P = .012) and LAVI (30.7 mL/m2, SD = 8.76 vs 24.6 mL/m2, SD = 6.57) (P = .002) than controls. Regression analysis showed that QTc and LAVI could correctly predict the presence of LPs in the 80.9% of the patients. Conclusions β‐TM patients have a higher prevalence of a prolonged PR interval, atrial fibrillation, and LPs. Twelve‐lead and SAECG performance was feasible in all subjects and constitutes a readily available tool for assessing myocardial electrophysiological alterations in this patient group. A cross‐sectional study considering the value of conventional and signal‐averaged electrocardiography in assessment of the arrhythmiological substrate of β‐thalassemia patients.